2012
DOI: 10.3109/00952990.2012.696168
|View full text |Cite
|
Sign up to set email alerts
|

Co-Occurring Psychiatric Symptoms in Opioid-Dependent Women: The Prevalence of Antenatal and Postnatal Depression

Abstract: Routine screening for perinatal and postpartum depression is indicated for women diagnosed with substance abuse disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 24 publications
(34 reference statements)
0
17
0
Order By: Relevance
“…132 Many women also live in substandard housing, are unemployed, and have a history of sexual abuse, intimate partner violence, or sexual assault. 133,134 Collaborative care offers the opportunity to address these and other co-occurring health issues during pregnancy. Interaction with different agencies and health-care providers who participate in a collaborative care coalition exposes these women to the possibility of continued care for themselves and their families throughout their lives.…”
Section: Collaborative Care Modelmentioning
confidence: 99%
“…132 Many women also live in substandard housing, are unemployed, and have a history of sexual abuse, intimate partner violence, or sexual assault. 133,134 Collaborative care offers the opportunity to address these and other co-occurring health issues during pregnancy. Interaction with different agencies and health-care providers who participate in a collaborative care coalition exposes these women to the possibility of continued care for themselves and their families throughout their lives.…”
Section: Collaborative Care Modelmentioning
confidence: 99%
“…On average, the participants self-reported surprisingly low levels of prenatal depressive and anxiety symptoms considering their high-risk situation and the accumulation of severe risks for prenatal mental disorders (Fellenzer and Cibula 2014;Lancaster et al 2010). The prevalence of prenatal depression was smaller at both time points compared to previous studies with similar samples (Holbrook and Kaltenbach 2012;Ordean et al 2013). Compared to results from a population-based birth cohort in Finland (Tolvanen et al 2013), the participants in the current study only reported slightly higher levels of prenatal anxiety and depressive symptoms, and mostly in the earlier phase of pregnancy.…”
Section: Discussionmentioning
confidence: 65%
“…Indeed, substance use while pregnant has been associated with a high level of prenatal stress (Woods et al 2010) and the prevalence of maternal perinatal mental disorders (Holbrook and Kaltenbach 2012;Strengell et al 2014). The prevalence of prenatal depression has been reported to be around 40-50% among substance using women (Holbrook and Kaltenbach 2012;Ordean et al 2013;Pajulo et al 2011a) which is high compared to an approximate prevalence of 10% in a normal population of pregnant women (Gavin et al 2005). Unfortunately, the comorbidity of substance use disorders and prenatal stress adversely affects maternal and fetal health through multiple divergent pathways.…”
mentioning
confidence: 99%
“…These findings are of significant public health importance, as previous research has shown individuals with mental health conditions are at an increased risk of developing substance use conditions 27,31,32 . Perinatal depression is one of the most common medical conditions related to pregnancy and childbirth in the United States 4‐6 .…”
Section: Discussion and Scientific Significancementioning
confidence: 86%